Wide-awake local anaesthesia no tourniquet (WALANT) procedures during COVID: a single centre experience - Sutcliffe, Alexandra; Khera, Bhavika; Khashaba, Haitham (Acta Biomedica Atenei Parmensis, 2022)
Background and aim WALANT procedures are becoming more popular, and are particularly useful in the COVID-19 pandemic. Procedures can be performed without needing access to general theatres and anaesthetic support, minimising the number of patient-healthcare interactions and avoiding aerosolisation. Our unit has taken this approach and aim to present a case series that demonstrates the efficacy and safety of WALANT. Methods A prospective analysis of WALANT cases in a single plastic surgery centre during March-August 2020 was performed. All procedures using a WALANT approach were included, that would have otherwise required general anaesthetic or regional block. Data was collected on a number of variables, including patient satisfaction. Results: 37 procedures were included in analysis. The majority of the injuries consisted of hand trauma. There were no cases of post-operative complications, although one required completion in main theatres due to technicality. No patients required additional anaesthetic during the procedure and all reported pain score as 0/10. Overall patient satisfaction was 10/10 for 26 patients, 9/10 for 10 patients and 7/10 for one patient. Conclusions Results show the use of WALANT can facilitate an effective plastic surgery trauma service during COVID-19. Most of the procedures were performed in the outpatient department setting, without the need for main operating theatres or anaesthetic support. All procedures were performed within 24 hours of initial presentation and were able to be discharged on the same day. In addition, patient satisfaction remained high and post-operative complications were minimal. We propose that the use of WALANT should continue and increase beyond the current pandemic.